PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (STUDI PADA KARYAWAN DIVISI INSPEKSI DAN PEMELIHARAAN PT HALEYORA POWER SALATIGA) - Rohmah, Dyah Nikmahtu; Widiartanto, Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2020)
PT Haleyora Power Salatiga is a subsidiary of PT PLN (Persero) engaged in operations and maintenance, which in 2018 the performance of the inspection and maintenance division employees did not reach the 100% performance target. Occupational safety and health in the company is suspected to be one of the factors that is not optimal because the protection of employees is not optimal. This type of research is explanatory research with a quantitative approach, using a sample of 50 respondents with data collection techniques using a questionnaire. Data analysis used validity test, reliability test, correlation test, determination test, simple and multiple regression analysis, t test, f test, and path analysis using SPSS 16.0. From the path analysis results it is known that the effect of work safety on employee performance through job satisfaction is greater (0.835) than the direct effect of work safety on performance (0.599). The effect of occupational health on employee performance through job satisfaction is also greater (0.710) than the direct effect of occupational health on performance (0.424). So it can be seen if the effect of occupational safety and health on employee performance will be greater if through job satisfaction. The author provides suggestions for PT Haleyora Power Salatiga, including providing face masks and storing used materials. The company also needs to conduct training for employees to become more skilled and work can be completed in the allotted time.